Effects of Administrative Law on Development Administration in Nigeria - Oikhala, Gabriel Izokpu; Aiya, Fidelix (NIU Journal of Humanities; Vol. 5 Núm. 4 (2020): KIU Journal of Humanities, Vol. 5 No. 4, December 2020, 2021)
The wild hardship of socio-economic problems in Nigeria has degenerated to label the country as poverty capital of the world. While insecurity agonies of prolonged failure of political leaders to provide good governance still blossom; corruption, brutality, and impunity of government officials also increase. Hence, the capacity of development administration to add value to public administration progressively deteriorated. This paper assessed the effects of administrative law on development administration in Nigeria. Data were gathered from relevant textbooks, journals, newspapers, and unpublished literature. Descriptive method was used to analyse the data. Adopting the rule of law approach as the conceptual framework; the paper identified political leaders, administrative law, and development administration as critical machineries for achieving the goals of the Nigerian state. The paper found the effect of administrative law on development administration as not good enough due to immense failure of political leaders to allow proper application of rule of law; change their priorities for self-service; and the overbearing corruption in Nigerian state. It recommended among others that the character of the Nigerian rulership should be re-branded from political dealers to leaders. Also, Nigerians should clamour for good leadership; vote for leaders with credentials and willingness to work for Nigeria; transform the country to where things work and where rule of law and good governance are not compromised. Keywords: Administrative Law, Social Control, Social Problems, Policy, Development, Development Administration, Administration of Development